PULSED NEUTRON LOGGING IN THE WORLD AND IN UKRAINE: BEGGINING, ESTABLISHMENT, PRESENT - PETROKUSHYN, Oleh; BEZRODNA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. At present, most of the oil and gas fields in Ukraine are depleted, requiring the operator companies in Ukraine to constantly monitor saturation levels and fluid movement withing the reservoirs as these are crucial pieces of information for optimizing and planning further production strategies. Methods. The development and current state of pulsed neutron logging as one of the main methods of monitoring the development of oil and gas fields is described in the paper. Results. The article focuses on the history of the establishment of the pulsed neutron logging, starting from 1949. Further development of the technology includes the creation of neutron generators, improvement of methods and equipment, as well as the appearance of modern multidetector tools. Two main types of pulsed neutron logging are considered: pulsed neutron-neutron logging and pulsed neutron gamma-logging, each has its own advantages and disadvantages. An important stage in the development of pulsed neutron logging was the creation of Sigma logging tools in the 1960s, which measure the neutron capture cross-section and are used to estimate the oil saturation of formation. A significant place in the paper is the analysis of the development of C/O-logging, which was first used in 1971 and determines the ratio of carbon to oxygen for estimating the oil saturation of rocks. The development of multi-detector tools made it possible to acquire logging data through tubing, which significantly expanded the possibilities of pulsed neutron logging. The achievements of domestic geophysicists in the development of pulsed neutron logging in Ukraine are also presented. Modern research is focused on the use of multi-detector tools and MCNP-models for quantitative determination of gas saturation in reservoir rocks. The use of these tools has shown high efficiency in the fields of the Dnieper-Donetsk basin and the Precarpathian depression. Conclusions. The article concludes that pulsed neutron logging plays a key role in the investigation and monitoring of cased oil and gas wells and suggests further steps for the development of this technology in Ukraine, including the introduction of new detectors, an increase in the number of detectors, and the use of MCNP models for more accurate determination of reservoir saturation.